Foreign Investment, Institutional Quality, Public Expenditure, and Activity of Venture Capital Funds in Emerging Market Countries (2014)
This paper empirically analyzes the effects of foreign direct investment (FDI), institutional quality, and the size of a government on venture capital (VC) activity. We conclude that institutional quality, FDI, and public spending have definitive importance as elements for the development of a public policy that increases the quantity and quality of VC fund (VCF) investment. Higher institutional quality, greater FDI, and lower public spending allow the volume of VCF investment to grow. FDI shows a higher level of significance in promoting investment in high-tech companies, and institutional quality increases the productivity of FDI investment in the generation of VCF. Government spending dramatically and (counter-intuitively) adversely affects the activities of VCF. Notably, the higher the institutional quality of a country, the less state intervention is required to promote investment of VCF. The results are consistent with the hypothesis of the FDI spillover and crowding out by public spending.